The Golden Age of China-Taiwan Relations: The Explanation and Its Future - Daniel Tantra Wiratama (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2017)
The past eight years since 2008 under the leadership of Ma Ying-jeou, the relations between China and Taiwan have been experiencing the golden age. By cooperating in many sectors, like economic partnership; social interactions; tourism and some political dialogues, both countries have been building a good relationship between them. Looking back to the past, China and Taiwan have a long series of conflicts, which ended in the Chinese Civil War 1949 with the victory of the Chinese Communist party which has now become the People’s Republic of China. Meanwhile, its opposing democratic party has now become the Republic of China (Taiwan). Since then, China and Taiwan’s relations have been on a standstill Ma Yingjeou rose to power as the president of Taiwan. By using the concept of Economic Interdependence and Conflict in World Politics by Mark J.C. Crescenzi, this paper aims to explain how the golden age of China-Taiwan relations have been going on in the past eight years up until now, as well as the future of the relations itself under the new president of Taiwan, Tsai Ing-we. This paper has the following research question: how has the good relation between China and Taiwan been built since 2008, considering their previously severed relations in the past?